2017
DOI: 10.1055/s-0037-1606334
|View full text |Cite
|
Sign up to set email alerts
|

The Facial Soft Tissue Effects of Orthognathic Surgery

Abstract: Orthognathic surgery is undertaken to correct anteroposterior, vertical, and transverse anomalies of the maxilla and mandible. Surgery has significant effects on the overlying soft tissue envelope. Some of these effects are beneficial while others may be detrimental to facial aesthetics. This review aims to update the reader on what soft tissue changes occur following orthognathic surgery to the mandible and maxilla. It is important to anticipate the detrimental effects of orthognathic surgery as this will all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
5
Order By: Relevance
“…The accuracy of superimposing the surface image of CBCT and the facial scan has been evaluated in previous studies, which reported that the image fusion was acceptable with a minimum error of less than 1 mm 18 , 19 . According to the literature, postoperative swelling is resolved by almost 80% after 6 months 20 . Additionally, we analyzed the images taken 6 months after surgery without debonding to minimize any unwanted effects, such as postsurgery swelling and ensure sufficient stabilization of the soft facial tissues.…”
Section: Discussionmentioning
confidence: 98%
“…The accuracy of superimposing the surface image of CBCT and the facial scan has been evaluated in previous studies, which reported that the image fusion was acceptable with a minimum error of less than 1 mm 18 , 19 . According to the literature, postoperative swelling is resolved by almost 80% after 6 months 20 . Additionally, we analyzed the images taken 6 months after surgery without debonding to minimize any unwanted effects, such as postsurgery swelling and ensure sufficient stabilization of the soft facial tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Orthognathic surgery significantly affects the contour of the facial, submental, and cervical soft tissues. 14 In some patients who underwent orthognathic surgery, postoperative esthetics of the face and neck area may not be satisfactory therefore additional soft tissue and/or skeletal treatment modifications incorporated into the treatment plan may be required. Numerous surgical techniques were defined to correct the esthetic problems in the submental-cervical region.…”
Section: Discussionmentioning
confidence: 99%
“…constant for both small and large displacements [27]. However, these results are difficult to generalize in simulations because of considerable interindividual variability [28]. Indeed, tissue changes depend on multiple parameters such as soft tissue thickness, muscle tone, the surgical techniques used… Nowadays, instead of displacement ratios, three-dimensional simulations of soft tissues are based on algorithms called approximation models that predict soft tissue displacements based on the forces applied [29].…”
Section: -Preoperative Simulation Of Soft Tissue Changesmentioning
confidence: 99%